Cell Proliferation (KI-67) Expression Is Associated with Poorer Prognosis in Nigerian Compared to British Breast Cancer Women. (11th April 2013) - Agboola, Ayodeji O. J.; Banjo, Adekumbiola A. F.; Anunobi, Charles C.; Salami, Babatunde; Agboola, Mopelola Deji; Musa, Adewale A.; Nolan, Christopher C.; Rakha, Emad A.; Ellis, Ian O.; Green, Andrew R.
Abstract : Background. Black women with breast cancer (BC) in Nigeria have higher mortality rate compared with British women. This study investigated prognostic features of cell proliferation biomarker (Ki-67) in Nigerian breast cancer women. Materials and Methods. The protein expression of Ki-67 was investigated in series of 308 Nigerian women, prepared as a tissue microarray (TMA), using immunohistochemistry. Clinic-pathological parameters, biomarkers, and patient outcome of tumours expressing Ki-67 in Nigerian women were correlated with UK grade-matched series. Results. A significantly larger proportion of breast tumours from Nigerian women showed high Ki-67 expression. Those tumours were significantly correlated with negative expression of the steroid hormone receptors (ER and PgR), p21, p27, E-cadherin, BRCA-1, and Bcl-2 (allP < 0.001 ), but positively associated with EGFR (P = 0.003 ), p53, basal cytokeratins: CK56, CK14, triple negative, and basal phenotype using Nielsen's classification (allP < 0.001 ) compared to UK women. Multivariate analyses showed that race was also associated with BCSS independent of tumour size, lymph node status, and ER status. Conclusion. Ki-67 expression was observed to have contributed to the difference in the BCSS in Nigerian compared with British BC women. Therefore, targeting Ki-67 in the indigenous black women with BC might improve the patient outcome in the black women with BC.